The globalization paradox democracy and the future of the world economy - Rodrik, Dani (W. W. Norton & Co., 2011)
Discusses how democracy and national self-determination cannot be pursued simultaneously with economic globalization and instead promotes customizable globalization with international rules to achieve balanced prosperity.